Tanggung Jawab Notaris Terhadap Akta Otentik Yang Penghadapnya Mempergunakan Identitas Palsu - Rahmad Hendra (Fakultas Hukum Universitas Riau, 2012)
Notary is a defender of truth and justice so that lawenforcement should be run in good faith and sincerity,so that the legal profession is an honorable and nobleprofession (officium nobile). The number of notariescreate tighter competition between notaries and no-tary sometimes make less careful in their profession.The paper concludes that the notary is responsible forwhat he saw, that they have seen, heard and done bythe notary as a public official in the run position. Nota-ries are not responsible if any information and docu-ments from a client that is not true